Implementation of self-tuning fuzzy PI controller on DCS for flow control system - Assawathanatorn, K.; Anuntahirunrat, K.; Chitwong, S. (My University, 2015)
In case of changing a communication between field instruments and controller from analog signal into digital signal or of changing a model of plant, performance of controller is degraded because of the fixed controller parameters such as PID controller. To solve this problem, a self-tuning PID controller is proposed. One of a popular self-tuning method is self-tuning fuzzy. Many researchers have been presented the self-tuning fuzzy PID controller. In this paper, we present implementing of self-tuning fuzzy PI controller for flow control system. Both fuzzy and PI controller is implemented on distributed control system (DCS) as controller at which communication between field instruments and distributed control system is via both the analog input and output modules as analog signal in range of 4-20mA and digital signal as Profibus PA. The PI controller parameters, proportional gain and integral time, from auto-tuning method is used to control plant, flow control system, by using analog signal at which result shows that flow process variable reaches to flow set point. The same PI controller parameters is applied for PROFIBUS PA at which results shows that flow process variable oscillates because of effect of delay-time taken place from communication between field instruments and distributed control system.
Keywords: Flow control system; FuzzyControl++ self-tuning fuzzy; PI controller; Process control system 7 (PCS7)